Allogeneic hematopoietic stem cell transplantation could improve the survival of acute myeloid leukemia patients with ASXL1 mutations. Issue 1 (1st January 2021) - Zhou, Lili; An, Jingnan; Hou, Chang; Ding, Zixuan; Qiu, Huiying; Tang, Xiaowen; Sun, Aining; Chen, Suning; Xu, Yang; Liu, Tianhui; Wu, Depei
ABSTRACT: Objective: To discover the function of allogeneic hematopoietic stem cell transplantation (allo-HSCT) in ASXL1-mutated acute myeloid leukemia (AML) patients. Methods: We analyzed the prognostic value of ASXL1 mutations and explored the role of allo-HSCT in 581 AML patients. Results: According to the definition of intermediate- and adverse-risk AML groups in the European Leukemia Net (ELN), ASXL1-mutated patients had shorter OS and DFS than ASXL1-wild-type patients in the intermediate- and adverse-risk AML groups (3-year OS: 47.5% vs. 60.8%, P<0.001; 3-year DFS: 28.5% vs. 48.9%, P<0.001). Among the cytogenetically normal acute myeloid leukemia (CN-AML), differences were found in both OS (47.4% vs.65.2%, P<0.001) and DFS (21.0% vs. 52.1%, P<0.001) between ASXL1-mutated patients and ASXL1 wild-type patients. In the ASXL1-mutated AML cohort, the patients received allo-HSCT had longer 3-year OS (P=0.0005) and 3-year DFS (P<0.0001) than those who did not receive allo-HSCT. Multivariate analysis revealed that ASXL1 mutation was an independent prognostic factor for OS (HR 2.248, 95% CI 1.155-4.375, P=0.017), and allo-HSCT had a positive impact on OS (HR 7.568, 95% CI 3.597-15.92, P<0.001) and DFS (HR 2.611, 95% CI 1.688-4.039, P<0.001) in ASXL1-mutated patients. Conclusion: The results indicate that the presence of ASXL1 mutations is a factor predictive of poor prognosis in AML patients and allo-HSCT could improve the survival of AML patients with ASXL1 mutations.